STRATEGIC STUDY OF THE IMPACT OF PANDEMIC ON INVESTMENT INSTRUMENTS IN THE UNITED STATES: THE CASE OF GOLD AND BITCOIN (Third Sector Social Economic Review, 2021)
The coronavirus has affected the whole world, espacially the economic balances of the countries as well as many sectors, including multinational companies. This situation has led to the questioning of the investment tools of the future. The Bretton Woods agreement in 1944 made countries dependent on the gold-dollar parity of the United States. The USA wants the currencies of other countries to be determined according to the value of gold and dollar. However, the digital money discourses of IMF and the US Government in recent years suggest whether a new investment tool will prevail in the world. Bitcoin, which emerged with the mortgage crisis in 2008, sustained its position after the 2019 pandemic. In this study, the effect of the pandemic on gold and bitcoin indices of the United States of America, which is one of the important determinants of the world market, has been investigated. A statistics package program was used in the study. According to the results of the research, it has been revealed that the pandemic has a positive effect on both gold and bitcoin. The interest in both investment instruments has been observed to be increased considerably, but dissemination of digital money is more focused on politics. It is predicted that this study will contribute to the literature in understanding the impact of the pandemic on investment instruments.
Keywords: Coronavirus; Covid-19; Digital Money; Bitcoin; Gold